Method for preparing carbon-coated transition metal material, carbon-coated transition metal material and application of carbon-coated transition metal material

By preparing carbon-covered transition metal materials, the shortcomings of transition metal materials in the prior art in terms of biocompatibility, stability and selective catalysis are solved, and the acid-base stability, biocompatibility and selectivity of the material are achieved. Improved, suitable for a variety of applications.

CN119407164APending Publication Date: 2025-02-11CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411505856.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing transition metal materials have shortcomings in biocompatibility, stability and selective catalysis, resulting in difficulties in life systems and catalysis processes.

Method used

By preparing carbon-coated transition metal materials, using carbon atoms to physically and chemically protect metal particles, enhancing the acid-base stability and biocompatibility of the material, and improving selectivity by regulating the electronic structure of metal atoms.

Benefits of technology

It has achieved the improvement of acid-base stability and biocompatibility of transition metal materials, enhanced the selectivity and stability of catalysts, and has strong ultraviolet-visible band absorption and magnetic properties, which are suitable for a variety of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119407164A_ABST
    Figure CN119407164A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a carbon-coated transition metal material, the carbon-coated transition metal material and application of the carbon-coated transition metal material, transition metal inorganic salt and an organic ligand are mixed and reacted to obtain metal organic framework powder, the metal organic framework powder is placed in Joule thermal equipment, the temperature is rapidly increased under protective gas, then the temperature is reduced to the room temperature, and the carbon-coated transition metal material is obtained. The carbon-coated transition metal material is obtained through post-treatment, the process is simple, the cost is low, and consumed time is short. The obtained carbon-coated transition metal material has acid-base stability and chemical stability; the absorption in the ultraviolet-visible wave band is strong, and a T2 imaging function is realized; according to the present invention, the material has characteristics of high selectivity, good biocompatibility and good magnetism on the substrate with the similar structure, and provides the excellent sensitivity and the excellent selectivity when the material is adopted as the working electrode so as to provide the scheme for the efficient selective catalysis; as a magnetic material, the material has the advantages of low cost, simple preparation, good biocompatibility and the like; the fluorescent quenching agent has the advantages of low cost, stability, high efficiency and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of transition metal materials, and in particular relates to a method for preparing a carbon-coated transition metal material, a carbon-coated transition metal material and an application thereof. Background Art

[0002] Transition metals refer to a series of metal elements in the d-zone and ds-zone of the periodic table (d-zone elements include elements of Groups IIIB to VIIB and VIII of the periodic table. Lanthanide and actinide elements are not included. ds-zone includes elements of Groups IB to IIB of the periodic table.).

[0003] Transition metal materials are widely used in many fields due to their low price and large reserves. For example, in the field of catalysis, transition metals are often used as catalysts and are widely used in oil refining, chemical and pharmaceutical industries. In the field of electronics, transition metals are used to manufacture electronic components. For example, copper is a common metal for making wires and contact materials, while metals such as tungsten, molybdenum, and niobium are used to manufacture devices such as semiconductors and electron tubes. In the field of life, transition metals are widely used as contrast agents, biomagnetic beads, etc. In addition, transition metals are also used in the manufacture of magnetic materials, liquid crystal displays, solar cells and other fields.

[0004] Existing transition metal materials play an important role in many chemical reactions, but there are also certain problems, such as:

[0005] Transition metal materials have poor biocompatibility due to the dissolution of transition metal ions, which greatly limits their application in living systems;

[0006] Transition metal materials are unstable and easily dissolved in acidic and alkaline environments, and are easily deactivated during the catalytic process;

[0007] Transition metal materials have poor selectivity as catalysts and have difficulty distinguishing substrates with similar structures, resulting in the inability to selectively react with the substrates. Summary of the invention

[0008] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0009] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0010] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a carbon-coated transition metal material.

[0011] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:

[0012] The transition metal inorganic salt and the organic ligand are dissolved in a solvent respectively, and the obtained transition metal inorganic salt solution and the organic ligand solution are mixed, and the mixture is stirred, allowed to stand, centrifuged, dried, and ground to obtain a metal organic framework powder;

[0013] The metal organic framework powder is placed in a Joule heating device, rapidly heated up under a protective gas and then cooled down to room temperature to obtain a crude product. The crude product is washed with acid and alcohol for multiple times to obtain a carbon-coated transition metal material.

[0014] As a preferred embodiment of the method for preparing the carbon-coated transition metal material of the present invention, the transition metal inorganic salt includes inorganic salts of cobalt, chromium, iron, manganese and nickel.

[0015] As a preferred embodiment of the method for preparing carbon-coated transition metal materials of the present invention, the organic ligand comprises one of 2-methylimidazole, trimesic acid, terephthalic acid and oxalic acid.

[0016] As a preferred embodiment of the method for preparing carbon-coated transition metal materials of the present invention, the solvent comprises one of anhydrous ethanol, water, acetone and methanol.

[0017] As a preferred embodiment of the method for preparing carbon-coated transition metal materials according to the present invention, the transition metal inorganic salt solution and the organic ligand solution are mixed, wherein the molar ratio of the transition metal inorganic salt to the organic ligand is 1:1 to 1:4.

[0018] As a preferred embodiment of the method for preparing carbon-coated transition metal materials described in the present invention, the metal organic framework powder is rapidly heated up under protective gas and then cooled down to room temperature, wherein the heating time is 0.1 to 5 seconds and the temperature is raised to 1500 to 3000°C.

[0019] As a preferred embodiment of the method for preparing carbon-coated transition metal materials according to the present invention, the cooling time to room temperature is 0.1 to 5 seconds.

[0020] Another object of the present invention is to provide a carbon-coated transition metal material.

[0021] The carbon-coated transition metal material has the following characteristics:

[0022] (i) Physical protection of transition metals based on carbon coating, which has acid and alkali stability, and chemical stability based on carbon atom intercalation of transition metal particles;

[0023] (ii) Strong absorption in the UV-visible band and T2 imaging capability;

[0024] (iii) It is selective for structurally similar substrates and has good biocompatibility and magnetic properties.

[0025] Another object of the present invention is to provide an application of a carbon-coated transition metal material.

[0026] The application includes the use of the carbon-coated transition metal material as a catalyst or a magnetic material or a fluorescence quencher or a contrast agent.

[0027] Another object of the present invention is to provide an electrochemical sensor, wherein the electrochemical sensor uses the carbon-coated transition metal material as a working electrode.

[0028] Beneficial effects of the present invention:

[0029] The present invention aims to provide a carbon-coated transition metal material to solve the following problems:

[0030] The method for preparing carbon-coated transition metal materials of the present invention has the characteristics of simple process, low cost, short time consumption, etc. Specifically, by carbon-coating transition metals, the transition metals are physically protected to avoid the dissolution of metal ions caused by direct contact between acids and bases, thereby solving the problems of unstable catalysts and poor biocompatibility; by intercalating transition metal particles with carbon atoms, stable coordination of carbon atoms to metal atoms is achieved, chemical stability of metal atoms is achieved, and the problems of unstable catalysts and poor biocompatibility are solved; by adjusting the electronic structure of transition metal atoms, selective detection of substrates with similar structures is achieved; the material has strong absorption in the ultraviolet-visible band and is magnetic, and can complete the separation and enrichment of biological molecules (nucleic acids, proteins, small molecules), etc.; when the material is used as a working electrode, it exhibits excellent sensitivity and selectivity, providing a solution for realizing efficient selective catalysis; as a magnetic material, it has the advantages of low cost, simple preparation, good biocompatibility, etc.; as a fluorescence quencher, it has the advantages of low cost, stability, high efficiency, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0032] Figure 1 The electron micrograph and X-ray diffraction pattern of the carbon-coated cobalt material prepared in Example 1 of the present invention.

[0033] Figure 2 The stability of the carbon-coated cobalt material prepared in Example 1 of the present invention in different solutions.

[0034] Figure 3 The carbon-coated cobalt material prepared in Example 1 of the present invention affects the activity of different biological cells.

[0035] Figure 4 This is the magnetic properties of the carbon-coated cobalt material prepared in Example 1 of the present invention.

[0036] Figure 5 This is the T2 (transverse relaxation time) weighted magnetic resonance imaging of the carbon-coated cobalt material prepared in Example 1 of the present invention.

[0037] Figure 6 The performance of the electrochemical sensor prepared using the carbon-coated cobalt material prepared in Example 1 of the present invention as the electrode material.

[0038] Figure 7 The ultraviolet absorption performance of the carbon-coated cobalt material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0040] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0041] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0042] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art.

[0043] Example 1

[0044] This embodiment provides a method for preparing a carbon-coated cobalt material, specifically:

[0045] 1) 14.5515 g of cobalt nitrate hexahydrate and 16.5216 g of 2-methylimidazole were dissolved in 50 mL of anhydrous ethanol (the molar ratio of inorganic salt to organic ligand was about 1:4), and the two solutions were mixed, stirred for 3 h, and then allowed to stand for 24 h. After standing, the solution was centrifuged at a temperature of 20 ° C, a speed of 6600 rpm, and a centrifugation time of 10 min. The solution was dispersed and centrifuged with anhydrous ethanol. After centrifugation for 4 times, the obtained material was dried in a drying oven at 60 ° C to obtain ZIF-67, which was ground into powder in a mortar to obtain metal organic framework powder, i.e., ZIF-67 powder;

[0046] 2) ZIF-67 powder is placed in a Joule heating device, evacuated and introduced with protective gas, the parameters are set to 2000°C, heating for 2s, cooling for 2s, and a wave number of 1, the temperature is rapidly raised to 2000°C, and then cooled to room temperature to obtain a crude product, i.e., a carbon-coated cobalt material containing impurities;

[0047] 3) Take 20 ml of 1M hydrochloric acid and add it to the carbon-coated cobalt material containing impurities, stir and let it stand for 6 hours, remove the supernatant, wash it repeatedly with 1M hydrochloric acid for 4 times, and then wash it repeatedly with anhydrous ethanol for 4 times, and dry the obtained material in a drying oven at 60°C to obtain the carbon-coated cobalt material (Co@C).

[0048] Figure 1 (a) is a scanning electron microscope image of the carbon-coated cobalt material obtained in this example, Figure 1 (b) is a transmission electron microscope image of the carbon-coated cobalt material obtained in this example. It can be seen that the obtained metal particles are evenly distributed and coated with a carbon layer. Figure 1 (c) is a high-resolution transmission electron microscope image of the carbon-coated cobalt material obtained in this example. It can be seen that the outer layer of the obtained metal particles is coated with a carbon layer. Figure 1 (d) is the X-ray diffraction image of the carbon-coated cobalt material obtained in this example, and it can be seen that the obtained particles have carbon present.

[0049] Application Testing

[0050] A: The carbon-coated cobalt material (Co@C) and cobalt nanoparticles (Co NPs) obtained in Example 1 were dispersed in artificial cerebrospinal fluid (aCSF) to prepare a 1 mg / ml suspension. The Co content in the supernatant was measured at different dispersion times. The results are as follows: Figure 2 As shown in (a), it can be seen that the cobalt particles are dissolved in the supernatant, proving that the content of the present invention has better stability than cobalt nanoparticles;

[0051] The carbon-coated cobalt material (Co@C) and cobalt nanoparticles (Co NPs) obtained in Example 1 were dispersed in 0.1M KOH to prepare a 1 mg / ml suspension. The Co content in the supernatant was measured at different dispersion times. The results are as follows: Figure 2 As shown in (b), it can be seen that the cobalt particles are dissolved in the supernatant, proving that compared with cobalt nanoparticles, the content of the present invention has better stability in an alkaline environment;

[0052] The carbon-coated cobalt material (Co@C) and cobalt nanoparticles (Co NPS) obtained in Example 1 were dispersed in 0.1 M HCl to prepare a 1 mg / ml suspension. The Co content in the supernatant was measured at different dispersion times. The results are as follows: Figure 2 As shown in (c), it can be seen that the cobalt particles are dissolved in the supernatant, proving that compared with cobalt nanoparticles, the content of the present invention has better stability in an acidic environment.

[0053] B. Mouse breast cancer cells were treated with Co@C (0-200 μg / ml) and cobalt nanoparticles (0-200 μg / ml) prepared in Example 1 for 24 h, then CCK-8 was added. Cell activity was measured 2 h later. The results are shown in Figure 3 As shown in (a), the increase in the concentration of cobalt nanoparticles causes the death of mouse breast cancer cells, while the material maintains high cell activity, proving that the product of the present invention has better biocompatibility than cobalt nanoparticles;

[0054] Schwann cells were treated with Co@C (0-200 μg / ml) and cobalt nanoparticles (0-200 μg / ml) prepared in Example 1 for 24 h, and then CCK-8 was added. Cell activity was measured after 2 h. The results are as follows: Figure 3 As shown in (b), the increase in the concentration of cobalt nanoparticles causes the death of neural Schwann cells, while the material maintains high cell activity, proving that the content of the present invention has better biocompatibility than cobalt nanoparticles.

[0055] C. Figure 4 (a) is the hysteresis loop of Co@C and Fe3O4 obtained in Example 1, Figure 4 (b) is the hysteresis loop of Co@C and Fe3O4 prepared in Example 1 at low field, which shows that the material has magnetism and can be used as a magnetic material.

[0056] D. Figure 5 This is the T2 (transverse relaxation time) weighted magnetic resonance imaging of the Co@C material obtained in Example 1. It can be seen that the material has T2 imaging performance and can be used as a contrast agent.

[0057] E. The Co@C material obtained in Example 1 (drop cast on a glassy carbon electrode as a working electrode, Ag / AgCl as a reference electrode, Pt as a counter electrode, and the differential pulse voltammetry (DPV) curves of different concentrations of dopamine (0-100 μM) in artificial cerebrospinal fluid (pH 7.4-7.5) were measured. The results are shown in Figure 6 (a) shows that the material can be used as an electrochemical sensor to quantitatively respond to dopamine;

[0058] The current-time response curves of different neuroactive substances (dopamine (DA), levodopa (L-DOPA), uric acid (UA)) in artificial cerebrospinal fluid (pH 7.4-7.5) were measured. The results are as follows Figure 6 As shown in (b), it can be seen that the material has a current response to the target molecule (dopamine) but no response to other interfering molecules, proving that the material can achieve a specific response to the detected object.

[0059] F. The Co@C material obtained in Example 1 was dispersed in an aqueous solution to prepare a 0.1 mg / ml dispersion, and the ultraviolet absorption spectrum at 200-800 nm was measured. The results are as follows: Figure 7 As shown, the material has full-band absorption properties for ultraviolet-visible light and can be used as a fluorescence quencher.

[0060] from Figure 2 to Figure 7 It can be seen from the application test results that the transition metal material prepared by the present invention is acid and alkali resistant, not easy to dissolve, and has improved biocompatibility and stability; it has good electrocatalytic performance and can complete electrochemical sensing of general chemical substances; it has good dispersibility and magnetism, can be used as biomagnetic beads to separate biological molecules, and can also be used as a contrast agent for magnetic resonance imaging; it has strong ultraviolet-visible absorption performance and can be used as a fluorescence quencher.

[0061] Example 2

[0062] The difference between this embodiment and embodiment 1 is that the temperature in the parameters of the Joule heat device in step 2) of embodiment 1 is adjusted to 1500° C., and the remaining steps and processes are all referred to embodiment 1 to obtain the carbon-coated cobalt material of this embodiment.

[0063] Example 3

[0064] The difference between this embodiment and embodiment 1 is that the type of organic ligand is adjusted to trimesic acid, that is, 14.5515g of cobalt nitrate hexahydrate and 16.5216g of 2-methylimidazole in embodiment 1 are adjusted to 14.5515g of cobalt nitrate hexahydrate and 13.5642g of trimesic acid (at this time, the molar ratio of inorganic salt to organic ligand is about 1:1.3), and the remaining steps and processes are all referred to embodiment 1 to obtain the carbon-coated cobalt material of this embodiment.

[0065] Example 4

[0066] The present embodiment provides a method for preparing a carbon-coated iron material, which is different from Example 1 in that the type of transition metal inorganic salt is adjusted to ferric chloride hexahydrate, and the type of organic ligand is trimesic acid, that is, 14.5515 g of cobalt nitrate hexahydrate and 16.5216 g of 2-methylimidazole in Example 1 are adjusted to 13.5148 g of ferric chloride hexahydrate and 16.5216 g of 2-methylimidazole (at this time, the molar ratio of the inorganic salt to the organic ligand is approximately 1:4), and the remaining steps and processes are all referred to Example 1 to obtain the carbon-coated iron material of the present embodiment.

[0067] Example 5

[0068] The present embodiment provides a method for preparing a carbon-coated nickel material, which is different from Example 1 in that the type of transition metal inorganic salt is adjusted to nickel nitrate hexahydrate, that is, 14.5515 g of cobalt nitrate hexahydrate and 16.5216 g of 2-methylimidazole in Example 1 are adjusted to 14.5393 g of nickel nitrate hexahydrate and 16.5216 g of 2-methylimidazole (at this time, the molar ratio of inorganic salt to organic ligand is about 1:4), and the remaining steps and processes are referred to Example 1 to obtain the carbon-coated nickel material of the present embodiment.

[0069] The application performance tests were conducted on the materials obtained in Examples 2 to 5, and the results were comparable to those in Example 1, and carbon-coated metal structures were obtained.

[0070] Comparative Example 1

[0071] The difference between this comparative example and Example 1 is that the heating temperature is adjusted to 4000°C, and the remaining steps and processes are all referred to Example 1. As a result, since the heating temperature is too high, far exceeding the boiling point of the metal, the transition metal volatilizes and the resulting product loses all the properties brought by the metal substance.

[0072] Comparative Example 2

[0073] The difference between this comparative example and Example 1 is that the heating temperature is adjusted to 500°C, and the remaining steps are all referred to Example 1. As a result, due to the low heating temperature, the organic ligand was not completely carbonized, and the color was light yellow powder, which was obviously different from the black color of the carbon material, so the experiment could not continue.

[0074] Comparative Example 3

[0075] The difference between this comparative example and Example 1 is that the heating time is adjusted to 0.01s, and the remaining steps are all referred to Example 1. As a result, due to the excessively fast heating rate and insufficient heat conduction, the organic ligand was not completely carbonized, and the color was light yellow powder, which was significantly different from the black color of the carbon material, so the experiment could not be continued.

[0076] Comparative Example 4

[0077] The difference between this comparative example and Example 1 is that the heating time is adjusted to 10s, and the remaining steps are all referred to Example 1. As a result, due to the slow heating rate, it is difficult to form a carbon-coated structure, making the metal unstable in an acidic and alkaline environment.

[0078] Comparative Example 5

[0079] This comparative example adopts chemical vapor deposition method to prepare carbon-coated cobalt material, specifically:

[0080] An appropriate amount of sodium hydroxide solution is gradually added to a 0.01M cobalt nitrate hexahydrate solution containing aluminum powder (the weight ratio of cobalt to aluminum is 1:19), the pH is adjusted to 8-10, and after standing for 4 hours, it is calcined at 200°C in an inert gas for 2 hours, and then placed in a tubular furnace. After the temperature is raised to 600°C under nitrogen, hydrogen is introduced for 2 hours, and then a mixed gas of methane and nitrogen (the volume fraction of methane is 12%) is introduced for 1 hour, and finally cooled under nitrogen to obtain a carbon-coated cobalt material.

[0081] Results Compared with the carbon-coated cobalt material prepared in Example 1 of the present application, the result obtained by this method is difficult to form a carbon-coated structure, making the metal unstable in an acidic or alkaline environment.

[0082] In summary, the method for preparing the carbon-coated transition metal material by the method of the present invention has the characteristics of simple process, low cost, short time consumption, etc. By carbon-coating the transition metal, the transition metal is physically protected to avoid direct contact of acid and alkali with the metal to cause the dissolution of metal ions, thereby solving the problems of unstable catalysts and poor biocompatibility; by intercalating carbon atoms into transition metal particles, the stable coordination of carbon atoms to metal atoms is achieved, the chemical stability of metal atoms is achieved, and the problems of unstable catalysts and poor biocompatibility are solved; by adjusting the electronic structure of transition metal atoms, selective detection of substrates with similar structures is achieved; the material has strong absorption in the ultraviolet-visible band and is magnetic, and can separate and enrich biological molecules (nucleic acids, proteins, small molecules), etc.; when the material is used as a working electrode, it exhibits excellent sensitivity and selectivity, providing a solution for achieving efficient selective catalysis; as a magnetic material, it has the advantages of low cost, simple preparation, and good biocompatibility; as a fluorescence quencher, it has the advantages of low cost, stability, and high efficiency.

[0083] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a carbon-coated transition metal material, characterized in that: include, The transition metal inorganic salt and the organic ligand are dissolved in a solvent respectively, and the obtained transition metal inorganic salt solution and the organic ligand solution are mixed, and the mixture is stirred, allowed to stand, centrifuged, dried, and ground to obtain a metal organic framework powder; The metal organic framework powder is placed in a Joule heating device, rapidly heated up under protective gas and then cooled down to room temperature to obtain a crude product. The crude product is washed with acid and alcohol for multiple times to obtain a carbon-coated transition metal material.

2. The method for preparing a carbon-coated transition metal material according to claim 1, characterized in that: The transition metal inorganic salts include inorganic salts of cobalt, chromium, iron, manganese and nickel.

3. The method for preparing a carbon-coated transition metal material according to claim 1, characterized in that: The organic ligand includes one of 2-methylimidazole, trimesic acid, terephthalic acid and oxalic acid.

4. The method for preparing a carbon-coated transition metal material according to claim 1, characterized in that: The solvent includes one of anhydrous ethanol, water, acetone and methanol.

5. The method for preparing a carbon-coated transition metal material according to claim 1, characterized in that: The transition metal inorganic salt solution and the organic ligand solution are mixed, wherein the molar ratio of the transition metal inorganic salt to the organic ligand is 2:1 to 1:

8.

6. The method for preparing a carbon-coated transition metal material according to claim 1, characterized in that: The metal organic framework powder is rapidly heated up under protective gas and then cooled down to room temperature, wherein the heating time is 0.1 to 5 seconds and the temperature is raised to 1500 to 3000°C.

7. The method for preparing a carbon-coated transition metal material according to claim 6, characterized in that: The cooling time to room temperature is 0.1 to 5 seconds.

8. A carbon-coated transition metal material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: It has the following characteristics: (i) Physical protection of transition metals based on carbon coating, which has acid and alkali stability, and chemical stability based on carbon atom intercalation of transition metal particles; (ii) Strong absorption in the UV-visible band and T2 imaging capability; (iii) It is selective for structurally similar substrates and has good biocompatibility and magnetic properties.

9. The use of the carbon-coated transition metal material as claimed in claim 8, characterized in that: The application includes the use of the carbon-coated transition metal material as a catalyst or a magnetic material or a fluorescence quencher or a contrast agent.

10. An electrochemical sensor, characterized in that: The carbon-coated transition metal material according to claim 9 is used as a working electrode.